The Treasury-Bill Futures Market - Jacobs, Rodney L.; Jones, Robert A. (Journal of Political Economy, 1980)
A model of the Treasury-bill futures market of the risk-premium augmented expectations variety is developed and estimated for the period March 1976 to July 1978. For that period we conclude that (1) futures interest rates deviate significantly from the corresponding forward rates implicit in the spot-market yield curve; (2) the hypothesis that expectations about the level of and trend in interest rates are formed adaptively from past spot rates fits the futures-market data significantly better than the hypothesis of perfect foresight; and (3) the risk-premium component of futures yields varies directly with time to delivery of the T-bills and negatively with the level of interest rates.